(untitled) (Psychology Travelogs, 2021)
The article is devoted to identifying the peculiarities of value attitude to health and determining ways to form the value attitude of senior students to their own health. The author reveals the essence of the concepts of «value», «value orientation», «value attitude», «health», «value attitude to health». It was found that the structure of the value attitude of high school students to their own health includes cognitive, emotionally-evaluated and behavioral components. In order to identify the peculiarities of the value attitude of high school students to their own health, a study was carried out using the «Health Attitude Index» methodology developed by S. Deryabo, V. Yasnev. It was found that in senior students, the cognitive component was the most pronounced, which indicates that high school students have the readiness and desire to receive, search and process information on health and healthy lifestyles; less formed is the emotional-evaluation component, manifested in aesthetic and ethical satisfaction from a healthy body, hypersensitivity, freedom from inadequate social aesthetic stereotypes, sensitivity to their own welcome manifestations and welcoming needs of other people; the least developed were practical and behavioral components, which indicates the low readiness of high school students to be included in various practical actions aimed at taking care of their health, as well as the reluctance of the younger generation to change their environment or affect it in accordance with their existing attitude to health. In order to form a value attitude of senior students to health, it is proposed to carry out psychological and pedagogical work in the following areas: working with parents of students; work with teachers who teach schoolchildren; direct impact on the value system of high school students.